Instructional Contextual Contestations in the Teaching of Chemical Equilibrium: A Multiple-case Study. Issue 2 (4th May 2019) - Kolobe, Lebala; Hobden, Paul
Abstract : In an ideal instructional context, one would expect the components (teacher, content and instructional strategy) to operate in harmony, in tandem and in a complementary manner. When these components are not in harmony, they are said to be in a state of 'instructional contextual contestation'. The components compete rather than complement each other. This article presents a multiple-case study of such contestations in the teaching of chemical equilibrium, a fundamental concept in chemical reactions that has been found to be difficult to teach. Four experienced teachers from three secondary schools with consistently impressive National School Certificate results were selected to participate as cases. Triangulated analysis and interpretation of data generated from biographical questionnaires, one-on-one interviews, classroom observations and document analysis were used to find teachers' created instructional contexts, using both individual and cross-case analyses. Interpretation of the results indicates that there are contextual contestations within and across cases. In particular, two components, assessed curriculum content and the nature of the teacher, dominated the context created in all cases. Teachers' strategy was showing and telling what learners needed for the examination: direct teaching, questioning, modelling and practising past questions. Only content that is normally assessed was taught: relevant terminology, application of Le Chatelier's Principle, related industrial processes and table method for Kc calculation. Therefore, the nature of chemical equilibrium and relevant instructional strategy used to teach the topic of chemical equilibrium became insignificant.